Contract costs, stakeholder capitalism, and ESG. (8th December 2020) - Fama, Eugene F.
Abstract: Observed contract structures are competitive solutions to the problem of maximizing stakeholder welfare when contracting is costly. Winning contract structures typically set fixed payoffs for most stakeholders, with residual risk borne by shareholders, who then get most of the decision rights. With rising interest in environmental, social, and governance (ESG) issues, there is sentiment for replacing the max shareholder wealth decision rule with max shareholder welfare. This view does not recognize that investors view max welfare in terms of their overall consumption‐investment portfolios. Since firms are not privy to the total ESG exposures of shareholders, max shareholder wealth is the appropriate decision rule.